2007
DOI: 10.1111/j.1365-2672.2007.03374.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low electric current (LEC) treatment on pure bacterial cultures

Abstract: Aims:  This research focused on the effects of low electric current (LEC) on the cell viability and metabolic activity of Escherichia coli and Bacillus cereus. Methods and Results:  Different LEC intensities at fixed amperage were applied, employing either graphite or copper electrode pairs, and the effects were determined by conventional cultural methods and bioindicators. On E. coli, the LEC with graphite electrodes at 5 and 10 mA led to no significant variation, but at 20 and 40 mA there was increasing inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…The use of electric current as a bacterial growth inhibitor was reported more than 40 years ago (24), with many subsequent reports over the years (27,30). Most of the literature on the subject deals with enhancement of the efficacy of antibiot- ics against microbial biofilms by the application of weak DC currents, a phenomenon termed "the bioelectric effect" by Costerton et al (5).…”
Section: Discussionmentioning
confidence: 99%
“…The use of electric current as a bacterial growth inhibitor was reported more than 40 years ago (24), with many subsequent reports over the years (27,30). Most of the literature on the subject deals with enhancement of the efficacy of antibiot- ics against microbial biofilms by the application of weak DC currents, a phenomenon termed "the bioelectric effect" by Costerton et al (5).…”
Section: Discussionmentioning
confidence: 99%
“…The positive or negative effects of DC mainly depend on current intensity, duration of treatment, and microbial type. For example, Valle et al (2007) investigated the electrolytic stimulation of Escherichia coli and Bacillus cereus and found that the application of 40 mA inhibited the cell growth and metabolic activities of E. coli, but enhanced that of B. cereus. These phenomena may depend on at least two parameters: current intensity and microorganism type.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an optimum current intensity may stimulate biodegradation of organic components, but lower or higher than it will have no impact or negative effects on pollutant biodegradation. In addition, the responses of different microorganisms (e.g., cell growth, enzymatic activity, and adenosine triphosphate (ATP) content) to the electrical stimulation are varied greatly (Valle et al 2007). Moreover, the extreme pH changes resulted from the water electrolysis reactions in the vicinity of the electrodes and high voltage values could inhibit the growth and activity of the microbes and lead to their death (She et al 2006;Lear et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Again, important for our purposes is the fact that dental surgery had recognized, and does today, this potential "electro-chemical" issue and its actions upon our implants, screw posts, other metals like amalgams, and crown and bridge metal restoration and its effect upon the oral cavity [2,3]. Related to this issue we present our Case Study.…”
Section: Progress In the Art And Science Of Dental Surgerymentioning
confidence: 99%
“…We offer patients in our practice neurological assessments for various facial non-specific pain by measuring the electrical dc output of metals with a potentiometer (multi-meter: measuring mV=millivolts, and uA=micro -amperage [1][2][3] (EAV assessment and acupuncture may be useful tools also. ).…”
Section: Future Options In Adhesive Dentistry: Case Studymentioning
confidence: 99%